Influência da vida séssil e planctônica no perfil de resistência antimicrobiana de Campylobacter jejuni isoladas de carcaças de frangos comercializadas no Brasil - Prado, Renata Resende (2017)
Campylobacter spp. is one of the most common bacterial etiological agents of food-borne gastrointestinal diseases worldwide. Among the species, C. jejuni is the most implicated in human disease when compared to C. coli and other ones. The main source of human infection for Campylobacteriosis is the consumption of contaminated food of animal origin, especially chicken meat. The dissertation was divided in two chapters, the first one referring to the general considerations that support the subjects discussed in the second chapter. Campylobacter virulence characteristics, biofilm formation, resistance to antibiotics and phylogeny were reviewed. In the second chapter, 30 strains of C. jejuni previously isolated from chicken carcasses produced by a Brazilian company with a complete production cycle, under federal inspection and qualified for export, were analyzed between 2015 and 2016. The susceptibility to antimicrobials of the isolates before and after the formation of biofilms in traditional culture medium and culture medium added with chicken juice, which simulates the nutritional conditions of the industrial environment. The technique used was the disc diffusion, and the results were used to create antimicrobial resistance profiles. Minimum inhibitory concentration (MIC) was performed for tetracycline using the broth microdilution technique. The genetic similarity between the strains was determined using the RAPD-PCR technique. To compare the resistance of the strains before and after biofilm formation (with and without chicken juice) in the diffusion test, the binomial test was used for two proportions, and for the MIC, the Friedman test, both with 95% probability.